Awareness of and attitude toward COVID-19 vaccination among individuals with COPD and the strategies to overcome vaccine hesitation: A mini review - Ying Liang; Yongchang Sun (Taylor & Francis Group, 2023)
ABSTRACTCoronavirus Disease 2019 (COVID-19) vaccines have a protective effect on individuals with chronic obstructive pulmonary disease (COPD), preventing them from developing severe illnesses and reducing the risk of hospitalization and mortality. However, the coverage rate of COVID-19 vaccination among this population is not satisfactory, which is associated with their lack of awareness of and negative attitudes toward COVID-19 vaccination, that is, vaccine hesitancy. We reviewed recent literatures on the vaccination status of COPD patients and vaccine hesitancy, described the factors related to vaccine hesitancy among COPD patients, and proposed strategies to improve the vaccine coverage, such as providing accurate and consistent vaccine information to the public, patient health education program, improving self-management capabilities, easy access to vaccination service, etc., which can hopefully help to improve patients' ability to cope with SARS-CoV-2 infection and reduce the COVID-19 related mortality.